1975
DOI: 10.1149/1.2134195
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Steady‐State Segregation under Zero Gravity: InSb

Abstract: A B S T R A C TIt was established that ideal, diffusion-controlled, steady-state segregation, never accomplished on earth, was achieved during the growth of Te-doped InSb crystals in Skylab. Surface tension effects led to nonwetting conditions u n d e r which free surface solidification took place in confined geometry. It was further found that, under forced contact conditions, surface tension effects led to the formation of surface ridges (not previously observed on earth) which isolated the growth system fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(40 citation statements)
references
References 0 publications
0
39
0
1
Order By: Relevance
“…Soon afterwards, Witt et al also found the separation growth of crystal when they researched the crystal growth and steady-state segregation of InSb under zero gravity. And they found that the crystal growing from the separate areas in both quality and performances was obviously better than the crystal growing using traditional technology [2]. Since then, Duffar and Regel explained the phenomenon of crystal growth separating from the crucible wall under microgravity condition [3], thus putting forward the detached solidification Bridgman method which combines the advantages of Czochralski method and Bridgman crystal growth method.…”
Section: Introductionmentioning
confidence: 99%
“…Soon afterwards, Witt et al also found the separation growth of crystal when they researched the crystal growth and steady-state segregation of InSb under zero gravity. And they found that the crystal growing from the separate areas in both quality and performances was obviously better than the crystal growing using traditional technology [2]. Since then, Duffar and Regel explained the phenomenon of crystal growth separating from the crucible wall under microgravity condition [3], thus putting forward the detached solidification Bridgman method which combines the advantages of Czochralski method and Bridgman crystal growth method.…”
Section: Introductionmentioning
confidence: 99%
“…"Dewetting" or "detachment" phenomenon was first observed spontaneously in space experiments during InSb Bridgman solidification performed on Skylab-NASA mission-1974 (Yue andVoltmer 1975;Wilcox et al 1975;Witt et al 1975). In dewetted Bridgman technique, the solid crystal is detached from the crucible wall by a small liquid meniscus at the level of the solid-liquid interface, creating a gap between the grown crystal and the crucible wall.…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion-controlled segregation in microgravity [1] can be disturbed by the residual micro acceleration [2], or bubbles [3,4]. Free surfaces and bubbles create a major disruption in fluid properties (e.g.…”
Section: Introductionmentioning
confidence: 99%